Skin Prick Reactivity among Asthmatics in East Africa - Kwizera, Richard; Wadda, Vincent; Mugenyi, Levicatus; Aanyu-tukamuhebwa, Hellen; Nyale, George; Gore, Robin; Kirenga, Bruce J. (World Allergy Organization Journal, 2020)
The burden of asthma in Africa is high, and yet the disease is not universally prioritised. Data on allergic asthma and its impact on asthma morbidity are limited in Africa. Our aim was to describe the distribution of skin prick positivity among asthmatics in Eastern Africa. From August 2016 to May 2018, 1671 asthmatic patients were enrolled from Uganda, Kenya, and Ethiopia as part of the African Severe Asthma Program clinical study. Skin prick testing was performed at baseline using a panel of 12 allergens, and factors associated with skin prick reactivity determined. Of the 1, 671 patients recruited, 71% were female with a median age of 40 years, 93.6% were aged >15 years and the patterns of asthma symptom frequency was intermittent in 2.9%, mild persistent in 19.9%, moderate persistent in 42.6% and severe persistent in 34.6% at baseline. Self-reported triggers, were dust (92%), cold weather (89%), upper respiratory infections (84%), strong smells (79%) and exposure to tobacco (78%). The majority (90%) of the participants had at least 1 positive allergen reaction, with 0.9% participants reacting to all the 12 allergens. Participants commonly reacted to house dust mites (66%), Blomia tropicalis (62%), and the German cockroach (52%). Patients sensitized to more allergens (>2) had significantly reduced lung function (FEV ≤ 80%; p = 0.001) and were more likely to visit the emergency department due to asthma (p = 0.012). There was no significant relationship between number of allergens and measures of asthma control, quality of life, and other clinical outcomes. Only the country of origin was independently associated with atopy among African asthmatics. There is a high prevalence of skin prick positivity among East African patients with asthma, with the commonest allergen being house dust mite. Skin reactivity did not correlate well with asthma severity and poor asthma control. The relation between atopy, measured through skin prick testing, and measures of asthma control among asthma patients in Eastern Africa is unclear and needs further study.
Keywords: Allergy, Atopy, Asthma, SPT, East Africa, Africa